Analisis Perlindungan Hukum terhadap Warna yang Diakui sebagai Merek Dagang dalam Hukum Internasional dan Hukum Nasional Indonesia - Joy Daniel Tarigan; Jelly Leviza; Fajar Khaify Rizky (Jurnal Hukum Lex Generalis, 2025)
Color protection as trademark faces harmonization challenges between international and national legal standards. The TRIPS Agreement recognizes color combinations with requirements of distinctiveness through secondary meaning and non-functionality, where developed countries like the United States and Australia even protect single colors as demonstrated in cases like Louboutin v. YSL. However, Indonesia through Law No. 20 of 2016 only recognizes "color arrangements" interpreted as combinations, hindering single color registration. Main obstacles include absence of technical guidelines for proving secondary meaning, imprecise color representation standards, high examiner discretion, and minimal jurisprudence. This creates legal vacuum and uncertainty for businesses, necessitating regulatory reform to recognize both single and combination color registration to provide legal certainty while aligning with international best practices.